Gus Dur : Islam, politik, dan kebangsaan - Moh. Mahfud M. D., 1957- (Yogyakarta : LKiS, 2010)
Thoughts of Abdurrahman Wahid on Islam, politics, and government in Indonesia; collected articles.
Includes bibliographical references (p. 257-260) and index.
Keywords: Abdurrahman, Wahid, -- 1940-2009 -- Religion; Abdurrahman, Wahid, -- 1940-2009 -- Political and social views; Islam and politics -- Indonesia